A Diagnostic Dilemma for the Pediatrician: Radiolucent Tracheobronchial Foreign Body - Hakan Taşkınlar; Gökhan Berktuğ Bahadır; Cankat Erdoğan; Doğakan Yiğit; Dinçer Avlan; Ali Naycı (Pediatrics and Neonatology)
The purpose of this study is to determine the role of clinical history, physical examinations, and radiological findings in the evaluation of patients with suspected radiolucent foreign body aspiration. Methods: The medical records of 236 children (under the age of 18 years), on whom a rigid bronchoscopy was performed between 1999 and 2015 because of suspected radiolucent foreign body aspiration, were analyzed retrospectively. Sensitivity, specificity, positive and negative predictive values of clinical history, physical examinations, and radiological findings were evaluated. Results: In 71.1% of all cases, the children were under the age of 3 years. The bronchoscopy showed the presence of a foreign body in 52.9% of cases, with the locations of the foreign bodies being as follows: (1) right main bronchus, 47.2%; (2) left main bronchus, 36.0%; (3) trachea, 11.2%; (4) both bronchi, 5.6%. Organic foreign bodies were found in 78% of the patients, whereas inorganic foreign bodies were detected in 22% of the patients. The sensitivity and specificity of clinical history, physical examinations, and radiological findings were 98.4% and 54.9%, 47.2% and 74.7%, and 35.2% and 92.7%, respectively. Conclusion: Tracheobronchial foreign body aspirations usually occur prior to the age of 3 years, with the most frequently aspirated foreign bodies being food or items of a radiolucent nature. Clinical history, physical examinations, and radiological findings are not able to detect the presence of a radiolucent foreign body aspiration in children. Therefore, a bronchoscopy should be performed on children in whom a choking event has been witnessed, even in cases of normal radiological and clinical findings.